2016
DOI: 10.1103/physrevfluids.1.064405
|View full text |Cite
|
Sign up to set email alerts
|

Scale dependence of the alignment between strain rate and rotation in turbulent shear flow

Abstract: The scale dependence of the statistical alignment tendencies of the eigenvectors of the strain-rate tensor e i , with the vorticity vector ω, is examined in the self-preserving region of a planar turbulent mixing layer. Data from a direct numerical simulation are filtered at various length scales and the probability density functions of the magnitude of the alignment cosines between the two unit vectors |e i ·ω| are examined. It is observed that the alignment tendencies are insensitive to the concurrent large-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
(65 reference statements)
1
10
0
Order By: Relevance
“…This implies that the most extensive strain at large scales is in the ξ 2 direction (4.1). Hence, small-scale vorticity and the large scale most extensive straining direction align, which is consistent with the observations in turbulent flows (Ishihara et al 2001;Hamlington et al 2008;Leung et al 2012;Fiscaletti et al 2016). The cross-over in alignment is determined by the point where the profiles of u 1 (ξ 1 ) and u 2 (ξ 2 ) cross, which is indicated in figure 15 by ×.…”
Section: Comparison With the High Reynolds Number Instantaneous Shearsupporting
confidence: 84%
See 2 more Smart Citations
“…This implies that the most extensive strain at large scales is in the ξ 2 direction (4.1). Hence, small-scale vorticity and the large scale most extensive straining direction align, which is consistent with the observations in turbulent flows (Ishihara et al 2001;Hamlington et al 2008;Leung et al 2012;Fiscaletti et al 2016). The cross-over in alignment is determined by the point where the profiles of u 1 (ξ 1 ) and u 2 (ξ 2 ) cross, which is indicated in figure 15 by ×.…”
Section: Comparison With the High Reynolds Number Instantaneous Shearsupporting
confidence: 84%
“…Earlier work has shown that small-scale vorticity preferentially aligns with the intermediate principal strain at small scales (Ashurst et al 1987). But when considering the larger-scale strain or the non-local strain, the same small-scale vorticity preferentially aligns with the most stretching principal straining direction (Ishihara et al 2001;Hamlington et al 2008;Leung et al 2012;Fiscaletti et al 2016). However, the exact scale at which the cross-over occurs is unknown.…”
Section: Comparison With the High Reynolds Number Instantaneous Shearmentioning
confidence: 98%
See 1 more Smart Citation
“…2012; Fiscaletti et al. 2016), which is physically related to the time lag in alignment elucidated by Xu, Pumir & Bodenschatz (2011). The Lagrangian behaviour of these terms deserves further consideration in future work.…”
Section: Efficiency Of the Energy Cascadementioning
confidence: 90%
“…Larger M brings the postshock PDF closer to the β vertex, while increasing Re λ opposes this trend. Prior studies in HIT (Danish & Meneveau 2018) and turbulent shear flows (Fiscaletti et al 2016) found better alignment of ω and β at small scales. Moreover, Gonzalez (2012) observed more efficient scalar mixing in HIT when ω and β are better aligned.…”
Section: Barycentric Map Representation Of Alignmentsmentioning
confidence: 81%